Studies on Ceric Tungstate Ion Exchanger - Sarkar, B.; Basu, S. (Asian Journal of Chemistry, 2010)
Synthesis and some interesting ion exchange properties of ceric tungstate are reported. The material, suitable for column operation, was used for the separations of several analytically binary mixture of cations.